ANALISIS PERILAKUKEPEMIMPINAN KEPALADINAS DALAMMENINGKATKAN EFEKTIFITAS ORGANISASI PEMERINTAHANKABUPATENROKANHULU - Noor, Auni M. (Jurnal Ilmu Administrasi Negara, 2016)
The role ofleadership in organization is very impotent. Therefore to succed a leaderhip isdepended on the competence to influence subordinate for full in effectivity of organization. Thisreseach is aim to know influence the behaviour of leadership on the effectivity of organization, atRokan Hulu Regency. Data is collected with survey method. The reseach population is the head ofofficers at Rokan Hulu Regency and from 60 (sixteen) employees are taken as sample with simplerandom sampling method. The data is analized by using cross tabulation. The result of reseach toknow that the behaviour leadership of the head of officers is enough good and organization effectivityis too enough effective. Correlation between the behaviour leadership with the organizationeffectivity is positive and significant.